2014
DOI: 10.1021/ml500298y
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Highly Potent Dual CysLT1 and CysLT2 Antagonist

Abstract: The benzoxazine derivative, (2S)-4-(3-carboxypropyl)-8-{[4-(4-phenylbutoxy)benzoyl]amino}-3,4-dihydro-2H-1,4-benzoxazine-2-carboxylic acid (19, ONO-2050297), was identified as the first potent dual CysLT1 and CysLT2 antagonist with IC50 values of 0.017 μM (CysLT1) and 0.00087 μM (CysLT2), respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…To understand the mechanism of ligand selectivity, we performed docking of 18 derivatives of the common 3,4-dihydro-2H-1,4-benzoxazine-2-carboxylic acid scaffold 30,31 with a large spectrum of CysLT 1 R/CysLT 2 R selectivity (Supplementary Table 3). Docking models of the most selective compounds in this structure-activity relationship (SAR) series 30 , cpd 13e (1,800-fold selective for CysLT 1 R) and cpd 15b (200-fold selective for CysLT 2 R), are shown in Fig. 3, alongside with cpd 11a (dual CysLT 1 R/CysLT 2 R), cocrystallized with CysLT 2 R, and pranlukast (4,500-fold selective for CysLT 1 R as shown in Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To understand the mechanism of ligand selectivity, we performed docking of 18 derivatives of the common 3,4-dihydro-2H-1,4-benzoxazine-2-carboxylic acid scaffold 30,31 with a large spectrum of CysLT 1 R/CysLT 2 R selectivity (Supplementary Table 3). Docking models of the most selective compounds in this structure-activity relationship (SAR) series 30 , cpd 13e (1,800-fold selective for CysLT 1 R) and cpd 15b (200-fold selective for CysLT 2 R), are shown in Fig. 3, alongside with cpd 11a (dual CysLT 1 R/CysLT 2 R), cocrystallized with CysLT 2 R, and pranlukast (4,500-fold selective for CysLT 1 R as shown in Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These data indicated that it was essential to possess two acidic groups for dual CysLT 1 and CysLT 2 antagonist activities. 19,33 Acylsulfonamide derivative 7 showed equipotent CysLT 2 antagonist activity compared with 1. Interestingly, tetrazole derivative 5 demonstrated significantly potent dual CysLT 1 and CysLT 2 antagonist activities, but it showed quite low permeability.…”
Section: Structure-activities Relationshipmentioning
confidence: 99%
“…The substitution reaction of reported ester analogue 28 19 with NH 3 in ethanol afforded 29. Reductive amination of 29 followed by dehydration afforded nitrile derivative 30.…”
Section: Chemistrymentioning
confidence: 99%
See 2 more Smart Citations